Navigating Communication Crossroads: Language Choice Dynamics in a Multinational Corporation Operating in Indonesia (Case Study: Riau Andalan Pulp and Paper) - Budiana, Agnes Arum; Ristra, Pretti; Kespandiar, Tengku (Politeknik Negeri Bengkalis, 2024)
This research explores the dynamics of language choice within a multinational corporation (MNC) operatingin Indonesia, specifically at Riau Andalan Pulp and Paper in Riau Province (RAPP). The study examines how employeesnavigate language choices between English, the corporate language, and Bahasa Indonesia, the local language, within amulticultural and multilingual workforce. Utilizing a mixed-methods approach, the study combines qualitative interviewswith quantitative surveys to gather comprehensive data from RAPP employees across various departments. Findingsreveal that English is predominantly used in formal settings, such as meetings and official documentation, reflecting itsrole as the corporate language. Conversely, Bahasa Indonesia is preferred for informal interactions, highlighting itsimportance in fostering employee comfort and social cohesion. Key factors influencing language choice includeprofessionalism, ease of communication, and inclusivity, with company policies promoting English proficiency to bridge cultural gaps. RAPP's language training initiatives, including the English Corner and participation in the Toastmasters Club, are instrumental in enhancing employees' language skills and supporting career development. The studyrecommends optimizing these programs by incorporating feedback, encouraging practical language use, leveragingtechnology, and aligning language learning with career advancement opportunities. By understanding and managinglanguage diversity, RAPP can enhance cross-cultural communication, contributing to its success in the global market.